ANALISIS KEBUTUHAN MODA ANGKUTAN UMUM BUS DI KABUPATEN TULUNGAGUNG - Mohammad Muhlis; Danang Wijanarko (JURNAL DAKTILITAS, 2022)
Abstract Transportation facilities and infrastructure services in Tulungagung Regency are recommended to overcome transportation problems that have not been able to give a big impact. The use of private vehicles must beㅤbalanced with theㅤdevelopment ofㅤpublicㅤtransportationㅤfacilities and infrastructure, namely buses. The bus mode of public transportation is one of the applications of traffic management by reducing the use of private vehicles used to carry out an activity with public transportation modes in the form of buses. Thisㅤstudyㅤaimsㅤtoㅤanalyzeㅤtheㅤcharacteristicsㅤofㅤtheㅤsocialㅤeconomy and the operational system of bus transportation. Theㅤmethodㅤusedㅤinㅤthisㅤresearchㅤisㅤtoㅤconductㅤaㅤfield survey by distributing direct interviews to related parties and questionnaires to respondents. The analysis used includes the analysis of the economic characteristics of the social community and the analysis of planning for public transportation modes. Theㅤresultsㅤofㅤtheㅤanalysisㅤthatㅤhasㅤbeenㅤcarriedㅤoutㅤby the authors obtained that most (74.6%) respondents use motorbikes to carry out activities. Most of them (54.3%) work and the result is that there are 5 planned routes for public bus transportation in Tulungagung Regency with cycle times between 95 to 250 minutes, and headway 15 minutes. Keywords:ㅤDegreeㅤofㅤsaturation;ㅤtrafficㅤvolume;ㅤroadㅤperformance; Abstrak Pelayanan saranaㅤdanㅤprasaranaㅤtransportasiㅤdi Kabupaten Tulungagung yangㅤdianjurkan guna mengatasiㅤpermasalahanㅤtransportasiㅤyangㅤbelum bisa memberikanㅤpengaruhㅤyang besar. Banyaknya penggunaan kendaraan pribadi harus di imbangi dengan pembangunan sarana dan prasarana angkutanㅤumumㅤyaitu bus. Moda angkutanㅤumumㅤbusㅤmerupakan salah satu penerapanㅤmanajemen laluㅤlintas denganㅤmengurangi penggunaan kendaraanㅤpribadi yangㅤdigunakan untuk melakukan suatu kegiatanㅤdengan moda transportasiㅤumum berupa bus. ㅤPenelitianㅤini bertujuan untuk menganalisa karakteristik ekonomi sosialㅤdanㅤsistemㅤoperasional transportasi angkutan umum bus. Metodeㅤyangㅤdigunakanㅤdalamㅤpenelitianㅤini dengan melakukan survey lapangan dengan cara penyebaran wawancaraㅤlangsungㅤkepadaㅤpihak-pihakㅤyang terkaitㅤdan kuisioner kepada responden. Analisa yang digunakan meliputi analisa karakteristik ekonomiㅤmasyarakat sosial dan analisa perencanaan moda angkutan umum. Hasil analisa yang sudah dilakukan penulis didapatkan sebagian besar (74,6%) responden menggunakan sepeda motor untuk melakukan aktivitas. Sebagian besar (54,3%) untuk bekerja dan hasilnyaㅤdiperolehㅤ5ㅤrencana trayekㅤangkutanㅤumum busㅤdiㅤKabupatenㅤTulungagung dengan siklus waktuㅤantara 95 sampai dengan 250 menit, dan headway 15 menit. Kata kunci: Sistem operasional; Perencanaan; Angkutan umum bus